Data mesh in action - Majchrzak, Jacek; Balnojan, Sven; Siwiak, Marian; Sieraczkiewicz, Mariusz (Manning Publications, 2023)
Revolutionize the way your organization approaches data with a data mesh! This new decentralized architecture outpaces monolithic lakes and warehouses and can work for a company of any size. In Data Mesh in Action you will learn how to: Implement a data mesh in your organization Turn data into a data product Move from your current data architecture to a data mesh Identify data domains, and decompose an organization into smaller, manageable domains Set up the central governance and local governance levels over data Balance responsibilities between the two levels of governance Establish a platform that allows efficient connection of distributed data products and automated governance Data Mesh in Action reveals how this groundbreaking architecture looks for both startups and large enterprises. You won't need any new technology--this book shows you how to start implementing a data mesh with flexible processes and organizational change. You'll explore both an extended case study and real-world examples. As you go, you'll be expertly guided through discussions around Socio-Technical Architecture and Domain-Driven Design with the goal of building a sleek data-as-a-product system. Plus, dozens of workshop techniques for both in-person and remote meetings help you onboard colleagues and drive a successful transition. About the Technology Business increasingly relies on efficiently storing and accessing large volumes of data. The data mesh is a new way to decentralize data management that radically improves security and discoverability. A well-designed data mesh simplifies self-service data consumption and reduces the bottlenecks created by monolithic data architectures. About the Book Data Mesh in Action teaches you pragmatic ways to decentralize your data and organize it into an effective data mesh. You'll start by building a minimum viable data product, which you'll expand into a self-service data platform, chapter-by-chapter. You'll love the book's unique "sliders" that adjust the mesh to meet your specific needs. You'll also learn processes and leadership techniques that will change the way you and your colleagues think about data. What's Inside Decompose an organization into manageable domains Turn data into a data product Set up central and local governance levels Build a fit-for-purpose data platform Improve management, initiation, and support techniques About the Reader For data professionals. Requires no specific programming stack or data platform. About the Authors Jacek Majchrzak is a hands-on lead data architect. Dr. Sven Balnojan manages data products and teams. Dr. Marian Siwiak is a data scientist and a management consultant for IT, scientific, and technical projects. Quotes This book teleports you into the seat of the chief architect on a data mesh project. - From the Foreword by Jean-Georges Perrin, PayPal A must-read for anyone who works in data. - Prukalpa Sankar, Co-Founder of Atlan Satisfies all those 'what', 'why', and 'how' questions. A unique blend of process and technology, and an excellent, example-driven resource. - Shiroshica Kulatilake, WSO2 The starting point for your journey in the new generation of data platforms. - Arnaud Castelltort, University of Montpellier